ANALYSIS OF MAGNETIC ANISOTROPY OF ROCK SAMPLES FROM THE POLIGON OF THE KRIVORIZKA EXTREMELY DEEP WELL - BEZRODNA, Iryna; BEZRODNY, Dmytro (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Understanding the reasons and principles of anisotropy of geological rocks opens the way to assess geodynamic processes in regions, enables to track changes of geological factors that form them, provides information about the structure and directions of the dynamics of geological rocks and etc. The aim of this study is the investigation of the nature of magnetic anisotropy of a collection of 26 samples that were taken from the well "Suputnyk-2" (490–2720 m) of the Kryvorizka extremely deep well. The samples consist of the following rocks: biotite schists, gneisses, ferruginous quartzites, muscovite quartzites, microcline-plagioclase granites. The authors used equipment of the KLY-2 series to measure the magnetic susceptibility of samples having the shape of cuberhombic decahedron. The authors have performed primary processing of measurement results and calculation of anisotropy parameters in the ANIZO10 program. The following parameters were determined as a result of the analysis: value of magnetic susceptibility (χ); statistical value of the standard deviation; normal values of magnetic susceptibility along three axes; coefficients characterizing magnetic anisotropy (H1 – H6); magnetic inclination angle (D) and magnetic inclination angle (I). The authors performed an initial classification of rocks based on the practical data processing scheme. Analyzing the calculations based on the ellipsoid of magnetic susceptibility, four rock classes were obtained: the shape of a sphere (12 %), a flattened shape (46 %), triaxial (23 %) and a complex ellipsoid shape (19 %). This indicates the complex geological conditions where rocks from the well "Suputnyk-2" (490–2720 m) were formed. It is confirmed that the samples belong to the VІІ–X tectonofacies according to the authors' previous research. The authors have investigated the coefficient of differential magnetic anisotropy, such as acoustic anisotropy. According to the results of the calculations, it was established that samples with low magnetic anisotropy are only 3.8 % of the total number of samples. Highly anisotropic samples of the collection comprise 53.8 % of the total number. It indicates the variety of processes that affected the rocks during their formation. According to the previous research of the authors, the coefficient of acoustic anisotropy of the well samples also varies from 2.8 to 24.9 %. The symmetry of the acoustic tensor in the majority of rock textures is rhombic. The final step in comparing the research results of the parameters of acoustic and magnetic anisotropy involved a tectonofacial analysis of the obtained data. It was determined that both magnetic and acoustic anisotropy coefficients, calculated from their respective tensors, reflect changes in tectonofacial conditions during the formation of the studied rocks.
Keywords: agnetic anisotropy; cuberhombic decahedron; classification; acoustic and anisotropy